« Le dernier procès allemand pour crimes de guerre » : L'ancien officier SS Julius Viel et le procès de Ravensburg d’avril 2001 comme événement médiatique - Vojtěch Kyncl (Criminocorpus)
In the second half of the twentieth century, the media played an important role in covering the trials of Nazi criminals. Regardless of the number of victims, the trials of Nazi criminals became media events that went beyond the usual scope of reporting on the just punishment of violent crimes. Did the 'last' German trial in 2001 against Julius Viel in Ravensburg, the name given to the trial of the murderer of seven Jewish prisoners near Litoměřice/ Leitmeritz in 1945, become a media event that closed a whole phase of work on Nazi crimes in Europe and North America? What information about the crime and its historical context, about the perpetrator, the key SS witnesses and the trial itself did the media coverage of the world's leading newspapers offer the general public? To what extent did it correspond to existing representations and knowledge about Nazi perpetrators, their actions and life after the war in Czech, German and Canadian societies?